A Case Report of Non-beverage Alcohol Abuse by Cooking Extract. Issue 4 (3rd July 2016) - Dayton, John Robert; Caravati, E. Martin; Smith, Spencer C.
ABSTRACT: A 14-year-old male presented to the emergency department with altered mental status. He was unable to protect his airway and required emergent intubation. Laboratory evaluation showed an elevated serum ethanol concentration of 233 mg/dL. The patient required care in a pediatric hospital intensive care unit. The patient's friends acknowledged that he consumed several small bottles of lemon cooking extract in order to become intoxicated. He chose lemon extract because the product label showed it had a higher alcohol concentration than the other available extracts. Cooking extracts are a relatively unregulated source of alcohol that can be purchased and abused by minors.